Intertemporal Labor Supply: A Household Collective Approach - José Alberto Molina; J. Ignacio Gimenez-Nadal; Jorge Velilla (Institute of Labor Economics (IZA), 2018)
This paper proposes an extension of the collective model for labor supply developed by Chiappori, Fortin and Lacroix (2002) to an intertemporal setting. We first develop a theoretical model to analyze the intra-household distribution of wealth in a multi-period framework, with a focus on labor supply and marriage markets. The model allows us to derive a sharing rule for non-labor income under a set of testable conditions. Second, using data from the Panel Study of Income Dynamics from years 1997 to 2015, we estimate the model using a semi-log parametrization of labor supply. Our empirical results do not reject the restrictions of the model, and point to the validity of the collective framework in an intertemporal setting. We show that wages are positively related to household labor supply, although cross and lagged effects show negative correlates. Furthermore, the ability of wives to negotiate the intra-household allocation of non-labor income is mainly driven by wages, with wives behaving altruistically, and husbands egoistically. Sex ratios appear to be nonsignificant in this relationship, although counteracting effects between labor and marriage markets may influence estimates.
Keywords: D15; J22; 330; household labor supply; collective model; intra household behavior; sex ratios; panel study of income dynamics